The role of separation on the forces acting on a circular cylinder with a control rod. (11th March 2021) - Cicolin, M.M.; Buxton, O.R.H.; Assi, G.R.S.; Bearman, P.W.
Abstract: Abstract : The development of the flow around a circular cylinder with a smaller diameter control rod in close proximity is the subject of this paper. It has long been known that this is an effective way to attenuate regular vortex shedding leading to reductions in its adverse effects on bluff-body flow. The aim of this study is to improve understanding of the ways the control rod affects the near-wake flow including how it influences the positions of boundary layer separation. Experiments were carried out in a water channel to measure lift and drag forces and particle image velocimetry (PIV) was employed to obtain detailed information on flow structure. The values of important properties were fixed as follows: Reynolds number, 20 000; ratio of cylinder and control rod diameters, 10 : 1; centre-to-centre distance between main cylinder and control rod, 0.7 D (where D is the main cylinder diameter). The adjustable parameter was the angular position of the rod, θ, which was varied between 90^° and 180^° from the front stagnation line. Lift and drag forces were measured separately for the main cylinder and the control rod. A new method for identifying flow states is introduced using PIV to interrogate the instantaneous flow velocity in the gap between the main cylinder and the control rod. Similarly to previous studies, three stable flow states were observed together with a bistable state. The bistable state is very sensitive to the control rod angle with a small change of ± 1^° being sufficient to change the flow state.